PENGEMBANGAN MEDIA MATERI GAGASAN POKOK BERBASIS SMART APPS CREATOR - Jauza, Ach.; Sujinah, Sujinah (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to determine the development of "basic idea" teaching materials based on Smart Apps Creator for sixth grade students at SDN Kalianget Timur I Sumenep, and also to describe the effectiveness of "basic ideas" teaching materials based on Smart Apps Creator for class VI students at SDN Kalianget Timur I Sumenep, and to analyze the practicality of "basic idea" teaching materials based on Smart Apps Creator for class VI students of SDN Kalianget Timur I Sumenep. This type of research uses research and development (R&D) methods with development procedures, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. Data collection techniques were carried out using media expert validation questionnaires, material expert validation questionnaires, and student response questionnaires. The results of research on the development of teaching materials based on Smart Apps Creator which were carried out in class VI semester II of SDN Kalianget Timur I, Kalianget District, Sumenep Regency, namely teaching materials for basic ideas based on Smart Apps Creator were developed, adjusting to the needs of the learning process. The need for teaching materials in the learning process is easy to use, in accordance with technology and student learning environment, interesting, and interactive. This can be seen in the display of the material which consists of writing, animation, video, working on practice questions, and can be used offline on a smartphone. In addition, the feasibility of teaching materials based on Smart Apps Creator was obtained which was developed according to the validator after being corrected according to the suggestions, which was very feasible. This can be seen based on the material aspect and the media aspect which obtained a percentage of 97% and 94% included in the very good/decent criteria, and the results of the student response questionnaire obtained a very good category with the percentage of student responses 95% (very good). Teaching the main ideas based on this Smart Apps Creator is declared practical.